Computed Tomography Guided Stereotactic Biopsy of Cerebral Lesion: A Safe Diagnostic Procedure (Nepal Journal of Neuroscience, 2016)
CT guided Stereotactic biopsy (CTSB) is a minimally invasive procedure that uses three dimensional (3D) coordinated system for precisely locating a target within a space to obtain tissue sample for diagnostic and therapeutic purposes.The main aim of this study is to analyze the role of CTSB in deep seated lesions, multi-focal lesions, lesions in eloquent areas as well as in frail patients at high risk for major cranial surgeries and small intra-cranial lesions which are otherwise hard to access.The study was conducted in National Institute of Neurological and Allied Sciences, Nepal with retrospective data using non probability purposive sampling.The study was done from January 2007 to December 2012. Analysis of frame based stereotactic biopsy over that period was done.Descriptive statistics for patient demographics and distribution of lesions was used. Paired t-test was used to compare pre-operative and post-operative GCS to define the safety. Difference in post procedure diagnosis in terms of histology was analysed.Of the 40 cases evaluated, 55% were males and 45% females. Lesions had lobar distribution in 62.5% and were deep seated in 37.5% cases. Three (7.5%) patients had multifocal lesions. Net diagnostic yield was 97.5% and diagnosis could not be established in one case. In fi ve (12.5%) cases the preoperative diagnosis was revised by the procedure and in 13 (32.5%) a new diagnosis was established. Complications were observed in 10%, 7.5% cases having seizure and 2.5% having postoperative brain swelling. Procedure related mortality was seen in one (2.5%) moribund patient. There was no statistical difference in GCS at 48 hours post procedure as compared to preoperative state implying the safety of the procedure.CTSB of cerebral lesion appears to be safe procedure of diagnostic advantage. It can significantly change the final diagnosis making it imperative when indicated.Nepal Journal of Neuroscience 12:14-19, 2015